PENERAPAN KOOPERATIF MODEL STAD KONSENTRASI GAYA KOGNITIF FI DAN FD UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA PADA MATA KULIAH KURIKULUM DAN BUKU TEKS SEJARAH DI JURUSAN SEJARAH FIS UNNES - ba'in, ba'in (Faculty of Social Science, Universitas Negeri Semarang, 2014)
The course Curriculum and History Textbooks generally less desirableand students tend to be passive in following the lecture. Cooperative learning is an appropriate method to help increase interest, activities and understanding of student learning. This method can be applied both to the student cognitive style FI and FD. With the expected student learning groups capable and aware that he has the potential to be developed. With a group learning activities students are required to take an active role and discipline so as to create a dynamic learning conditions which in turn students' understanding of the learning materials increased.Having applied the method cooprative learning increases studentactiveness STAD model. At baseline 77.5% still have a low interest in cycle 1 student interest increased to 69.91% higher, and in cycle 2 to 24.9% and 60% very high high. Similarly, students also increased the activity of completely inactive following the lecture on pre-cycle becomes active (62.5%) and very active (12.5%) in cycle 1 and cycle 2 increased to aktof (52.5% ) and very active (47.5%). To increase student understanding of the FI there is an increasing understanding of 49.33% in the pre cycles to 72.86% in cycle 1, and increased to 81.90% in cycle 2. As for the FD students there is an increasing understanding of 47, 00% on pre-cycle into 67.14% in cycle 1, and increased to 78.86% in the second cycle.